Análise da performance de relé de proteção digital - RODRIGUES, Mauricio Matheus Livramento (2019)
Protection relays are devices that monitor the Electrical Power System, comparing the real parameters with their preset. When detecting abnormalities, it acts directly on an equipment or a system, removing from operation the equipment or components involved with the abnormality, in addition to triggering alarm circuits when necessary. The protection systems are essential for the equipment integrity conservation belonging to the electrical systems and for the maintenance of its proper functioning. In this sense, it is fundamental that the protection relays provide a planned performance, making important the process of evaluating the performance of these devices. Several benefits have been incorporated into the protection systems through the introduction of digital relays, such as reliability and the possibility of programming more complex protection functions. These benefits were also accompanied by the evolution of relay performance evolution methods. This work shows the characteristics and the evaluation performance procedures of digital relays. Thereunto, the performance of the RET 670 digital relay manufactured by ABB was studied, tested and analyzed. For the tests with the protection device, real parameterization data applied into protection system of a metallurgical plant, located in the southeast of the state of Pará, connected in the National Interconnected System, were used. Based on these data, differential function tests were performed. To improve the understanding of the evaluation process, this work also presents a review regarding the relays and its protection main functions.